Exploring the Life and Legacy of Stephen Haskell: Pioneer of Adventist Theology and Education - Hutabarat, Franklin (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2025)
Stephen Haskell (1833–1922) was a pivotal figure in the early development of the Seventh-day Adventist Church, making profound contributions to its theology, evangelistic efforts, and educational framework. This research investigates Haskell’s life and legacy, with a focus on his role as a theological pioneer and educational advocate. Haskell’s early conversion to the Adventist faith set the stage for his significant involvement in spreading the movement's message. As one of the church’s first theologians, Haskell helped shape core Adventist doctrines, particularly through his influential works on Biblical interpretation and the relationship between prophecy and Adventist beliefs. In addition to his theological contributions, Haskell’s vision for Adventist education played a crucial role in the establishment of schools that were designed to offer both spiritual and academic development. His support for educational institutions was instrumental in shaping a system that emphasized holistic learning, grounded in Christian principles. This research also highlights Haskell's leadership in early missionary efforts, particularly in the establishment of churches and outreach initiatives across North America. By analyzing Haskell's writings, missionary endeavors, and leadership within the church, this study explores his lasting influence on both Adventist theology and education. Haskell’s multifaceted contributions laid the foundation for the growth of Adventism in the 20th century, with his emphasis on theological integrity and educational advancement continuing to resonate in Adventist institutions today. Ultimately, Stephen Haskell's legacy as a pioneer of Adventist thought and education remains central to the identity of the Seventh-day Adventist Church.